Tourism as a factor of demand in public road passenger transportation in the Republic of Croatia - Kos, Goran, inženjer prometa (Array, 2020)
The paper presents the results of research in tourism as one of the most important factors in the public passenger transport demand. The research has been carried out for the requirements of creating a Tourism Satellite Account (TSA) for the Republic of Croatia for 2016. Traffic and tourism, as strategic economic activities of the Republic of Croatia, have the characteristics of complex and dynamic systems, mutually conditioned by the guidelines of the demand and supply chain of tourist product values. Therefore, the paper is oriented towards the analysis of the significance of tourism for public road passenger transport in the Republic of Croatia. During 2016, road intercity passenger transport carried 50.4 million passengers, out of which 98 percent in domestic and 2 percent in international transport. Passenger road transportation is marked by mild seasonal oscillations, with the summer period marked by the lowest level of demand, and the period from January to March by the largest number of passengers. The provision of public road transportation services in 2016 realised a revenue of 1.8 billion kuna for 433 business subjects registered in this activity. The trends indicate an increase in the number of travelled kilometres by buses with passengers.